2020
DOI: 10.1016/j.molp.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Shunts Replenish the Calvin–Benson–Bassham Cycle as Anaplerotic Reactions in Cyanobacteria

Abstract: The recent discovery of the Entner-Doudoroff (ED) pathway as a third glycolytic route beside Embden-Meyerhof-Parnas (EMP) and oxidative pentose phosphate (OPP) pathway in oxygenic photoautotrophs requires a revision of their central carbohydrate metabolism. In this study, unexpectedly, we observed that deletion of the ED pathway alone, and even more pronounced in combination with other glycolytic routes, diminished photoautotrophic growth in continuous light in the cyanobacterium Synechocystis sp. PCC 6803. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 43 publications
(65 reference statements)
6
88
1
Order By: Relevance
“…This pathway allows conversion of glucose to the oxidative PP intermediate 6-P-gluconate, which is then converted into glyceraldehyde-3-P. The ED pathway is required for optimal photoautotrophic growth and glycogen catabolism, and possibly also optimal activity of the CBB cycle [41].…”
Section: Catabolism Of Glucose and Glycogenmentioning
confidence: 99%
“…This pathway allows conversion of glucose to the oxidative PP intermediate 6-P-gluconate, which is then converted into glyceraldehyde-3-P. The ED pathway is required for optimal photoautotrophic growth and glycogen catabolism, and possibly also optimal activity of the CBB cycle [41].…”
Section: Catabolism Of Glucose and Glycogenmentioning
confidence: 99%
“…Studies have shown that cyanobacteria employ the EMP pathway for degradation of glucose residues to pyruvate [30]. This is also the case for growth in dark phases [31]. Furthermore, the EMP produces less NADPH and more ATP, compared to other glycolytic routes, such as the OPP (oxidative-pentose-phosphate pathway) or the ED (Entner-Doudoroff) pathway.…”
Section: Physiological Function Of Phbmentioning
confidence: 99%
“…We also observed downregulation of the terminal proteins in the phycobilisomes, suggesting modified harvesting of light energy to alleviate excitation pressure on the photosynthetic system. Under these conditions, inhibition of photoassimilation is compensated by glycolysis of stored glucose and CBB intermediates, providing an important supply of substrates for anaplerosis of the CBB and TCA cycles during acclimation to the transition [83,114,115]. In the current work, enhanced glycolytic activity is indicated by the upregulation of NDH-1, suggesting an increased reliance on respiratory electron transport for ATP generation, while strong downregulation of PEP synthase and PFOR after CO 2 stepdown may prevent diversion of pyruvate away from the TCA cycle.…”
Section: Altered C/n Balance Modulates the Energetic Strategy Of Nostmentioning
confidence: 99%